THE EXISTENTIALIST FOUNDATIONS OF VYTAUTAS KAVOLIS’ LIBERALISM - Noreika, Alvydas (Politologija, 2016)
The article deals with philosophical foundations of the theory of Liberalism developed by the Lithuanian-American sociologist and one of the leaders of the Lithuanian diaspora in the USA Vytautas Kavolis (1930–1996). It aims to clarify the problem of coherence which Kavolis encounters while developing his political theory and the way of dealing with it by him. The problem is conditioned by the fact that the thinker seeks to develop Integral Liberalism, which would encompass not only Liberalism, but other modern political ideologies as well, especially Conservatism. By taking fundamental differences between Liberalism and Conservatism into account, the question arises about the possibility of their reconciliation and of the establishment of Integral Liberalism as a coherent system of thought and action. It is stated that Kavolis looks for conditions of both possibilities in the area of philosophical anthropology. The thinker’s conception of man is grounded on a presupposition that the fundamental structure of human existence consists of the self and the world. The self is this particular, unique, autonomous and free individual. The world is the sum total of relationships. At the center of this totality stands the national community and its cultural tradition. The relationship between the self and the world is defined in two ways. On the one hand, they are not deducible from one another, therefore they are separate elements of human existence. On the other hand, the self and the world are interrelated. They cannot exist without one another. The community and its cultural tradition fill the self with content. They provide the self with meanings, which enable an individual to live meaningfully. It is supposed that the self is incapable to create meanings by itself. In one’s turn, the community could not be alive without the self. Kavolis’ conception of man presupposes a defined existential ontology of Liberalism, Conservatism and Integral Liberalism. According to it, Liberalism has roots in the self, Conservatism – in the world, and Integral Liberalism is rooted in the whole structure of human existence. There is no conflict between Liberalism and Conservatism on the fundamental level of human existence. They are in accordance because their existential grounds, i.e., the self and the world, are not only separate, but also interrelated entities. Liberalism and Conservatism are involved in conflict when their meaning is overemphasized and efforts are made to establish them as all-embracing ideologies. If there is no real conflict between Liberalism and Conservatism, then Integral Liberalism is possible as a consistent system of thought and action, too.